1906
DOI: 10.1017/s0080456800035523
|View full text |Cite
|
Sign up to set email alerts
|

XXV.—On the Hydrodynamical Theory of Seiches

Abstract: § 1. The variations of the surface-level of lakes due to the direct action of wind and rain, and the smaller disturbances caused by surface waves, of small or moderate length, due to the action of the wind and the movement of boats and animals, must have been familiar phenomena at all times. The first accurately recorded observation, that lake-levels are subject to a rhythmic variation, similar in some respects to the ocean tides, seems to have been made at Geneva in 1730 by Fatio de Duillier, a well-known Swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1953
1953
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…It is essentially a modern implementation of Chrystal's graphical method of residuation (Chrystal, 1906), with an excellent introduction and review provided by Huang and Wu (2008). In contrast to Fourier decomposition employing time-invariant sinusoidal bases, wavelet transforms using scale-invariant wavelets, or empirical orthogonal functions based on eigenmodes, EMD is a recursive residuation extracted from envelopes of the data itself.…”
Section: Introductionmentioning
confidence: 99%
“…It is essentially a modern implementation of Chrystal's graphical method of residuation (Chrystal, 1906), with an excellent introduction and review provided by Huang and Wu (2008). In contrast to Fourier decomposition employing time-invariant sinusoidal bases, wavelet transforms using scale-invariant wavelets, or empirical orthogonal functions based on eigenmodes, EMD is a recursive residuation extracted from envelopes of the data itself.…”
Section: Introductionmentioning
confidence: 99%
“…To find the X and x of (5 .17) Chrystal (1906) has shown that both surface shape and depth profile are important in determining the free motion of a lake. Proudnan and Doodson (1924) considered the dynamic response of sea-level due to variations in both atmospheric pressure and wind stress but only for a basin of rectangular surface and uniform depth.…”
Section: ¿2 Internal Seiche Motionsmentioning
confidence: 99%
“…For example, the problem of the free oscillations of a fluid in an elongated basin has been solved by Chrystal (1906) for a number of regularly shaped depth profiles, while Defant (1918) solved this problem for variable shaped basins using a finite difference technique. This latter method is reported in Pefant (1960).…”
Section: Introduction General Considerationsmentioning
confidence: 99%
“…This is equivalent to the equations used by Chrystal (1905) and Defant (192^), and several methods have been given for obtaining a solution.…”
Section: Seiche Equations -One Dimensional Theorymentioning
confidence: 99%